FROM THE MYTHOLOGY OF THE RUSSIANS OF DAGESTAN: DOMOVOY - Seferbekov, Ruslan Ibragimovic (History, Archeology and Ethnography of the Caucasus, 2024)
The article, based on field ethnographic material and literary sources collected in the villages of the Kizlyar and Tarumovsky districts of Dagestan using general scientific historical (chronological, historical-genetic, comparative-historical, structural-diachronic, retrospective) and special methods of ethnology (survey, interviewing), provides an analysis (hypostases, loci of habitation, time of appearance, methods and forms of communication with a person, patronage and malicious actions, amulets) of the ambivalent mythological character of Russian mythology - the brownie. The similarities and differences between the brownies among the Russians of Dagestan and the Russians of the main ethnic massif, as well as among the peoples of Dagestan, the North Caucasus and the world are explored. The origin of this mythological image among the Slavs dates back to the collapse of the primitive neighboring community, the establishment of patriarchy, and the emergence of households with their large and small families. The mythological character of the brownie is based on the veneration of dead ancestors and the cult of the hearth. Later (medieval and modern times), this contradictory and syncretic image absorbed new features and characteristics. This indicates that ideas about the brownie were formed in different historical eras and indirectly reflect the social, socio-economic and cultural processes that took place among the Eastern Slavs in different chronological periods. The ambivalence of the brownie is explained by his belonging to three vertical sacred spaces (upper world - middle world - underworld), as well as to temporal (past - present - future), genealogical (ancestors - current generation - descendants) and etiological (favorable - neutral - unfavorable) spheres. The brownie’s belonging to the upper divine world imposed on him the responsibilities of the patron of the home and family, and his relationship to the underworld gave him the functions of strangling a person during the demon’s sleep. Sacred continua and chronotopes allowed profane time and space to be permeable for the penetration of otherworldly characters into our world.